Electronic properties of DNA-related molecules containing a bromine atom. (2nd January 2023) - Hirato, Misaki; Onizawa, Misato; Baba, Yuji; Haga, Yoshinori; Fujii, Kentaro; Wada, Shin-ichi; Yokoya, Akinari
Abstract: Purpose: To clarify the radiosensitization mechanism masking the Auger effect of the cells possessing brominated DNA, the electronic properties of DNA-related molecules containing Br were investigated by X-ray spectroscopy and specific heat measurement. Materials and Methods: X-ray absorption near-edge structure (XANES) and X-ray photoemission spectroscopy (XPS) were used to measure the electronic properties of the nucleotides with and without Br. We determined the specific heat of 5-bromouracil crystals with thymine as a reference molecule at low temperatures of 3–48 K to calculate the microscopic state numbers. Results: Obtained XANES and XPS spectra indicated that both the lowest unoccupied molecular orbital (LUMO) and the core-levels were not affected by the Br incorporation. The state numbers of 5-bromouracil calculated from the specific heats obtained around 25 K was about 1.5 times larger than that for thymine below 20 K, although the numbers were almost the same below 5 K. Discussion: Our results suggest that the Br atom may not contribute substantially to the LUMO and core-level electronic states of the molecule, but rather to the microscopic states related to the excitation of lattice vibrations, which may be involved in valence electronic states.